Religious education and containment of radical elements: the case of Malaysia - Fathil, Fauziah; Oktasari, Wiwin (International Islamic Schools Alliance (ITTISHAL), 2016)
The occurrence of many events involving radical or militant elements today caused a concern that education too might have been used by some irresponsible groups to spread their radical ideas in order to recruits followers or supporters. In some Muslim countries today, this is what that has happened and is taking place where young people including youths and young children are taught to hate other people of different beliefs or ideologies and trained on how to handle weapons. In Malaysia, while phenomenon involving radical ideas is generally under control, still there have been some allegations that a certain style of education particularly of pondok system being involved in militant-related activities. Based on primary and secondary sources, this paper attempts to seek out reasons for such allegations, highlighting certain issues and prior events that happened in the country which might have contributed to these contentions. The paper also provides possible means and ways, in view of the scenario in Malaysia, in making sure that religious education in the country remains free from the unwanted radical elements or ideas.